77.8k views
3 votes
Step by step what is 4 (x - 1) -3 (x + 2)

2 Answers

4 votes

Step one: 4(x-1)-3(x+2)=0 (set equal to zero)

Step two: 4x-4-3x-6=0 (multiply numbers on the outside to inside of "( )")

Step three: x-10=0 (combine like terms)

Step four: 0+10=10, x=10 (inverse operation)

Answer: x=10

User Charl Botha
by
5.6k points
4 votes

Answer:

For this expression, you will have to use the distribution property to get your answer.


First, distribute the 4 to the x and -1


4(x)=4x


4(-1)=-4



4x-4-3(x+2)

Now do the same with the -3, x and 2


-3(x)=-3x


-3(2)=-6



4x-4-3x-6

Now combine like terms to get your final answer


4x-3x=x


-4-6=-10


Thus, your solution is: x - 10


User Quuxplusone
by
6.1k points